2014
DOI: 10.3759/tropics.23.111
|View full text |Cite
|
Sign up to set email alerts
|

Water storages in plants and soils in two community forests of Karen tribe, northern Thailand

Abstract: This study aims to evaluate the roles of community forests managed for different purposes on water storages in plants and soils as the basic information for watershed management. Community forests of Karen people in Chiang Mai province, northern Thailand, were divided to conservation (CF) and utilization (UF) forests. These community forests were classified as pinemontane and montane forests. The number of tree species in the CF and the UF was 256 and 132, respectively. Shannon-Wiener Index in the CF (4.5±0.6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Within 100 cm soil, this soil had the MWHC of 5,113.74 m 3 /ha. This value was nearly the same to the deep soil of Order Ultisols in the lower montane forest, 4,956 m 3 /ha (Khamyong et al, 2014a). Sumanochitraporn et al (2014) found that the deep soil (the Ultisols) in a 22-year-old teak plantation could store the lower amount of water at 3,617.60 m 3 /ha while the Ultisols under the 22-year-old three needle pine had the higher value of 5,632.87 m 3 /ha (Khamyong et al, 2014b).…”
Section: Contribution Of Planted Pine To Plant Biomass and Water Storagesupporting
confidence: 66%
See 2 more Smart Citations
“…Within 100 cm soil, this soil had the MWHC of 5,113.74 m 3 /ha. This value was nearly the same to the deep soil of Order Ultisols in the lower montane forest, 4,956 m 3 /ha (Khamyong et al, 2014a). Sumanochitraporn et al (2014) found that the deep soil (the Ultisols) in a 22-year-old teak plantation could store the lower amount of water at 3,617.60 m 3 /ha while the Ultisols under the 22-year-old three needle pine had the higher value of 5,632.87 m 3 /ha (Khamyong et al, 2014b).…”
Section: Contribution Of Planted Pine To Plant Biomass and Water Storagesupporting
confidence: 66%
“…As for the degraded lower montane forest which had the amount of biomass at 79.48 Mg/ha, the contribution of pine to the biomass was high as 67.94% of the total. Khamyong et al (2014a) studied water storage in the lower montane forest in northern Thailand. The community forest of Karen village was divided into the conservation forest (CF) and the utilization forest (UF).…”
Section: Contribution Of Planted Pine To Plant Biomass and Water Storagementioning
confidence: 99%
See 1 more Smart Citation